2017
DOI: 10.1177/1558944717701238
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Biomechanical Properties, Repair Times, and Value of Common Core Flexor Tendon Repairs

Abstract: The braided cruciate was the strongest of the tested flexor tendon repairs. The 2-mm gapping and maximum load to failure for this repair approached similar historical strength of other 6- and 8-stranded repairs. In this study, suture cost was negligible in the overall repair cost and should be not a determining factor in choosing a repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…36 Although several epitendinous suture patterns have been used for flexor tendon repairs in human patients, the most common consist of continuous and interlocking horizontal mattress patterns because of their ease of placement after primary core suture repair. 17 Therefore, this pattern was adapted for canine tendon repair in our study. The primary mode of failure in this study was suture pull through, which occurred in 59.7% of constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Although several epitendinous suture patterns have been used for flexor tendon repairs in human patients, the most common consist of continuous and interlocking horizontal mattress patterns because of their ease of placement after primary core suture repair. 17 Therefore, this pattern was adapted for canine tendon repair in our study. The primary mode of failure in this study was suture pull through, which occurred in 59.7% of constructs.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] The patterns most commonly used for primary tendinous repair in dogs are the 3LP or LL. 16 In publications on human flexor tendon repair, it has been reported that the strength of the repair site is directly proportional to the number of suture strands crossing the repair site, 17 with sutures placed in the epitenon increasing the strength of the repair by 10% to 50% compared with core suture placement alone. 18 Epitendinous, or circumferential, tendon repair was first introduced in man in the 1960s and later refined.…”
Section: Introductionmentioning
confidence: 99%
“…Although TDABC may be an accurate measurement of cost analysis, the use of institutional cost and minutes of operating time and cost of major materials to estimate the total procedure cost remains a cost analysis that remains popular in the literature. 5 As hospitals move toward a value-based care model, with value defined as outcomes divided by costs, accurate and standardized tracking of procedural costs must be better defined as these figures will continue to grow in importance. 12 PSI also significantly decreased the tourniquet time in our study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other cost analysis methods used to measure effectiveness have been based on operating room (OR) charges, billing costs, cost of materials, and out-of-pocket cost paid by payers. 5,16 Similarly, estimates of OR time per minute and other input variables used in cost analysis vary widely. 6 We are not aware of any other studies comparing TDABC to other cost analysis methodologies in TAA.…”
Section: Introductionmentioning
confidence: 99%
“…Passing bidirectional barbed suture through the tendon to maximize passes with one suture aligns portions of the barbs to resist tendon distraction, that is, separation of the repaired tendon with tensioning, with other suture portions not providing resistance to distraction. [12][13][14][15][16] The previous biomechanical studies investigating barbed suture have shown that the ultimate load and 2-mm gap force were comparable but not superior to standard knotted sutures, 12,13 possibly due to underutilization of the barbs to prevent distraction.…”
Section: Introductionmentioning
confidence: 99%